Scenario of investing the surpluses of official reserves of Iraq in gold for the period (2010-2021): Scenario of investing the surpluses of official reserves of Iraq in gold for the period (2010-2021) - Lateef , Shurooq; Abass, Aqeel (The Gulf Economist, 2023)
This study aims to present an alternative investment portfolio to invest the surplus from the official reserves of Iraq, by proposing an alternative portfolio that invests the surplus in gold and comparing it with the actual portfolio. Miscellaneous lead to the growth of reserves and increase cash receipts and then sustain them.